Penerapan Modifikasi Alat dan Media Pembelajaran dalam Menigkatkan Keterampilan Passing Bawah Bola Voli - Risno, Risno; Safari, Indra; Saptani, Entan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The aim of this research is to improve these skills by applying modifications to learning tools and media. The method used is Classroom Action Research using the Kemmis and McTaggart model which includes planning, action, observation and reflection. The sample used was 19 class V students at SDN Citimun II, 11 boys and 8 girls. This research uses an assessment rubric instrument. The results of the research can be seen in cycle I, 8 students or 42.2% succeeded in showing progress. In cycle II, the number of successful students increased to 11 students or 57.8%. Furthermore, in cycle III, there was a significant increase with 16 students or 84.2% successfully achieving the target. Conclusion is that by applying modified tools and media in learning volleyball underpassing, it can significantly improve the skills of fifth grade students at SDN Citimun II in practicing volleyball underpassing. Keywords: modification of learning tools and media, underpassing, volleyball games